2014
DOI: 10.1007/s11869-014-0265-8
|View full text |Cite
|
Sign up to set email alerts
|

Traffic-related pollution and asthma prevalence in children. Quantification of associations with nitrogen dioxide

Abstract: Ambient nitrogen dioxide is a widely available measure of traffic-related air pollution and is inconsistently associated with the prevalence of asthma symptoms in children. The use of this relationship to evaluate the health impact of policies affecting traffic management and traffic emissions is limited by the lack of a concentration-response function based on systematic review and meta-analysis of relevant studies. Using systematic methods, we identified papers containing quantitative estimates for nitrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 32 publications
1
53
0
2
Order By: Relevance
“…The prominent focus on NO 2 in the literature is probably related to the wide availability of this pollutant measure, the ease and relatively low cost to measure it and its relative specificity to road traffic [30]. The focus on NO 2 in air quality guidelines, plans and mitigation strategies in the EU, and beyond, is perhaps reinforcing the study of this pollutant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prominent focus on NO 2 in the literature is probably related to the wide availability of this pollutant measure, the ease and relatively low cost to measure it and its relative specificity to road traffic [30]. The focus on NO 2 in air quality guidelines, plans and mitigation strategies in the EU, and beyond, is perhaps reinforcing the study of this pollutant.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a hand search in the reference lists of all the included studies and of previous relevant reviews we identified [15,17,23,24,25,26,27,28,29,30]. We contacted authors of unpublished studies (abstracts only) and the authors of the most recurrent studies to ensure the inclusion of all relevant published material on the topic and this resulted in the inclusion of two additional studies [31,32].…”
Section: Methodsmentioning
confidence: 99%
“…The past 20 years have seen a significant increase in the prevalence of asthma in children (Tang et al, 2015). The pathogenesis of asthma is related to multiple risk factors including environmental factors such as vehicular pollution, and genetic factors such as polymorphisms in the interleukin (IL)-4 and ORMDL3 genes (Favarato et al, 2014;Tang et al, 2014;Zhai et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Each LSOA within an middle layer super output area was assigned the same baseline rate of events. Dose response functions from meta‐analyses and studies recommended by Committee on the Medical Effects of Air Pollutants (COEMAP) link change in pollution exposure in each area to change in incidence of pollution‐linked disease (Cesaroni et al, ; Colbourn et al, ; Department of Health Medical Directorate Respiratory Team, ; Favarato et al, ; Hoek et al, ; Mangham, Petrou, Doyle, Draper, & Marlow, ; Pedersen et al, ; Sapkota, Chelikowsky, Nachman, Cohen, & Ritz, ; Schikowski et al, ; World Health Organisation, ). These determine the absolute number of cases averted for each LSOA, according to the size and age structure of the population in each local authority reported in the 2011 Office for National Statistics census .…”
Section: Methodsmentioning
confidence: 99%